Sol-gel synthesis of Fe₂O₃-doped TiO₂ for optimized photocatalytic degradation of 2,4- dichlorophenoxyacetic acid - Razani, Afini (Oriental Scientific Publishing, 2017)
Fe₂O₃-doped and undoped TiO₂ catalysts were synthesized by sol-gel method and used to optimize the photocatalytic degradation of 2,4-Dichlorophenoxyacetic acid (2,4-D). The catalysts produced were dominated by the tetragonal, crystalline anatase TiO₂ cell structure. The 0.05wt% Fe₂O₃-doped TiO₂ catalyst exhibited higher photocatalytic activity than that of undoped TiO₂ but its performance decline with increase Fe₂O₃ content due to possible increase of recombination centers. Photocatalytic degradation of 2,4-DA was optimized by response surface methodology. The highest 2,4-DA degradation (48%) was obtained when 1.0 g of 0.05wt% Fe₂O₃-doped TiO₂ is used to degrade 10 ppm of 2,4-DA at pH 4.